Modified Hemocyanins from Rapana thomasiana and Helix aspersa Exhibit Strong Antitumor Activity in the B16F10 Mouse Melanoma Model - Emiliya Stoyanova; Nikolina Mihaylova; Nikola Ralchev; Silviya Bradyanova; Iliyan Manoylov; Yuliana Raynova; Krassimira Idakieva; Andrey Tchorbanov (Marine Drugs)
Melanoma is one of the most common tumors worldwide, and new approaches and antitumor drugs for therapy are being investigated. Among the promising biomolecules of natural origin for antitumor research are gastropodan hemocyanins—highly immunogenic multimeric glycoproteins used as antitumor agents and components of therapeutic vaccines in human and mouse cancer models. A murine melanoma model established in C57BL/6 mice of the B16F10 cell line was used to study anticancer modified oxidized hemocyanins (Ox-Hcs) that were administered to experimental animals (100 μg/mouse) under different regimens: mild, intensive, and with sensitization. The solid tumor growth, antitumor response, cell infiltration in tumors, and survival were assessed using flow cytometry, ELISA, and cytotoxicity assays. Therapy with Ox-RtH or Ox-HaH resulted in the generation of enhanced specific immune response (increased levels of tumor-infiltrated mature NK cells (CD27+CD11b+) in sensitized groups and of macrophages in the intensively immunized animals) and tumor suppression. Beneficial effects such as delayed tumor incidence and growth as well as prolonged survival of tumor-bearing animals have been observed. High levels of melanoma-specific CTLs that mediate cytotoxic effects on tumor cells; tumor-infiltrating IgM antibodies expected to enhance antibody-dependent cellular cytotoxicity; type M1 macrophages, which stimulate the Th1 response and cytotoxic cells; and proinflammatory cytokines, were also observed after Ox-Hcs administration. The modified Hcs showed strong antitumor properties in different administration regimens in a murine model of melanoma with potential for future application in humans.